Association Between Metabolic Syndrome and Radiographic Hand Osteoarthritis: Data From a Community‐Based Longitudinal Cohort Study. Issue 3 (30th January 2018) - Strand, Mette P.; Neogi, Tuhina; Niu, Jingbo; Felson, David T.; Haugen, Ida K.
Abstract : Objective: To explore whether metabolic syndrome and its components are associated with hand osteoarthritis (OA) using longitudinal data from the Framingham Study. Methods: Our cross‐sectional analyses included 1, 089 persons (ages 50–75 years), of whom 785 had longitudinal radiographs obtained 7 years apart. Of these, 586 with no hand OA at baseline were included in analyses of hand OA incidence. We explored associations between metabolic syndrome and its components (central obesity, hypertension, diabetes mellitus, triglyceridemia, and low high‐density lipoprotein) and radiographic hand OA (defined as ≥2 interphalangeal joints with a Kellgren/Lawrence [K/L] grade of ≥2) using logistic regression analyses with adjustment for age, sex, and body mass index. In longitudinal analyses, metabolic syndrome was used as a predictor for change in K/L sum score and incident hand OA. Results: Metabolic syndrome was not associated with the presence of hand OA (odds ratio [OR] 1.11 [95% confidence interval (95% CI) 0.78–1.59]), change in K/L sum score (OR 0.83 [95% CI 0.59–1.17]), or incidence of hand OA (OR 0.91 [95% CI 0.58–1.44]). Hypertension was borderline significantly associated with the presence of hand OA (OR 1.25 [95% CI 0.90–1.74]), and a significant association was found between hypertension and change in K/L sum score (OR 1.47 [95% CI 1.08–1.99]). Consistent dose‐response relationships were not demonstrated (data not shown). Furthermore, hypertension was not significantly associated with hand OA incidence (OR 1.23 [95% CI 0.82–1.83]). No significant associations were found between metabolic syndrome and erosive hand OA. Conclusion: We found no association between metabolic syndrome and hand OA. The role of hypertension in hand OA pathogenesis warrants further investigation.